Assisting female artists and architects : a user centered approach adopted by Design Library, University of Dammam, Kingdom of Saudi Arabia / Saima Qutab and Raed Al-Bukhari - Qutab, Saima; Al-Bukhari, Raed (Faculty of Information Management, 2014)
This study is to investigate the information needs and services expectations of artists and archtiects from Design College Library in Saudi Arabia. Researchers used mix method of research. The findings were later translated into services and resources to support teaching and research. This is the uniqness of this study that it narrates the research findings' implications into practicality.